Scalable synthesis of a foam-like FeS2 nanostructure by a solution combustion-sulfurization process for high-capacity sodium-ion batteries - Hu, Rudan (2021)
Pyrite-type FeS2 is regarded as a promising anode material for sodium ion batteries. The synthesis of FeS2 in large quantities accompanied by an improved cycling stability, as well as retaining high theoretical capacity, is highly desirable for its commercialization. Herein, we present a scalable and simple strategy to prepare a foam-like FeS2 (F-FeS2) nanostructure by combining solution combustion synthesis and solid-state sulfurization. The obtained F-FeS2 product is highly uniform and built from interconnected FeS2 nanoparticles (∼50 nm). The interconnected feature, small particle sizes and porous structure endow the product with high electrical conductivity, good ion diffusion kinetics, and high inhibition capacity of volume expansion. As a result, high capacity (823 mA h g−1 at 0.1 A g−1, very close to the theoretical capacity of FeS2, 894 mA h g−1), good rate capability (581 mA h g−1 at 5.0 A g−1) and cyclability (754 mA h g−1 at 0.2 A g−1 with 97% retention after 80 cycles) can be achieved. The sodium storage mechanism has been proved to be a combination of intercalation and conversion reactions based on in situ XRD. Furthermore, high pseudocapacitive contribution (i.e. ∼87.5% at 5.0 mV s−1) accounts for the outstanding electrochemical performance of F-FeS2 at high rates.